Strategi Peningkatan Penerimaan Pajak Daerah Melalui Pembentukan Satuan Tugas Pajak Daerah Oleh Badan Pendapatan Daerah Kabupaten Takalar - Wijaya, I Made Aldy (Jurnal Pallangga Praja (JPP), 2023)
Regional taxes are a support in financing the implementation of local government and regional development. The Regional Revenue Agency of Takalar Regency as the Regional Apparatus Organization (OPD) responsible for local tax management seeks to increase regional revenue from the local tax sector. One of the efforts made is the formation of a Regional Tax Task Force (Satgas). This study aims to describe the strategy of increasing local tax revenue carried out by the Regional Tax Task Force of Takalar Regency. This research uses a qualitative research approach with a descriptive method. Data collection techniques are by interviews (in depth interviews), observation, and documentation. Informants selected by purposive sampling method include agency heads, field heads, subfield heads in Takalar County Regional Revenue Agency and tax collectors. Data analysis techniques with methods from Miles and Huberman include data reduction, data presentation, and conclusions. The results showed that the implementation of the program to increase local tax revenue by the Takalar Regency Regional Tax Task Force had run optimally. However, there are several inhibiting factors such as lack of public awareness and lack of apparatus resources within the Regional Revenue Agency. The efforts made by the Regional Tax Task Force are the implementation of massive socialization and building an IT-based regional tax management environment.